2000
DOI: 10.1124/mol.58.3.535
|View full text |Cite
|
Sign up to set email alerts
|

Selective Activation of the c-Jun N-Terminal Protein Kinase Pathway during 4-Hydroxynonenal-Induced Apoptosis of PC12 Cells

Abstract: The by-product of lipid peroxidation, 4-hydroxynonenal (HNE), was shown to cause apoptosis in PC12 cells. In this study, we investigated the molecular mechanism of HNE-induced apoptosis in these cells. Specifically, we determined the effect of HNE on the activities of mitogen-activated protein (MAP) kinases involved in early signal transduction. Within 15 to 30 min after HNE treatment, c-Jun N-terminal protein kinase (JNK) was maximally activated, before it returned to control level at 1 h post-treatment. In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 41 publications
2
88
0
Order By: Relevance
“…Levonen et al found that HNE could conjugate with Keap1 in vivo, and the author proposed that this might be the underlying mechanism of HNE-mediated Nrf2 nuclear translocation [72]. Nonetheless, since HNE has been found to activate various signaling pathways including PKC [73][74][75][76][77][78][79], the possibility of Nrf2 phosphorylation by HNE-mediated signaling pathways cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Levonen et al found that HNE could conjugate with Keap1 in vivo, and the author proposed that this might be the underlying mechanism of HNE-mediated Nrf2 nuclear translocation [72]. Nonetheless, since HNE has been found to activate various signaling pathways including PKC [73][74][75][76][77][78][79], the possibility of Nrf2 phosphorylation by HNE-mediated signaling pathways cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…The redox regulation of MAPK pathways has been well known (203) and numerous studies have clearly shown that pathophysiological concentration of HNE (1-25 μM) could increase the phosphorylation/activity of the major three MAPK pathways (204)(205)(206)(207)(208)(209)(210).…”
Section: B Mapk Activation By Hnementioning
confidence: 99%
“…In contrast, Song et al reported that HNE more likely activated JNK through targeting upstream kinases. They found that HNE-mediated JNK activation could be abrogated with the dominant-negative inhibition of stress-activated protein kinase kinase 1 (SAPKK1 or SEK1), the upstream kinase of JNK that was also activated by HNE (205). It should be noted however, that modification of the upstream protein kinases by HNE directly has not been demonstrated.…”
Section: B Mapk Activation By Hnementioning
confidence: 99%
“…However, the inhibition of ERK1/2 activation has been shown to protect a mouse neuronal cell line and rat primary cortical neurons form oxidative stress-induced neurotoxicity [1] demonstrating a possible involvement in cell death. The JNK signaling cascade has been reported to be activated by a wide range of different oxidants/reductants including hydrogen peroxide [135,218], lipid peroxidation products [6,191], different types of radiation [63], modulators of intracellular glutathione status [145], peroxynitrite [71], glutamate [180], dithiothreitol, and nitric oxide [152]. Although the links between redox status and MAPK signaling have been known for some time, data demonstrating the molecular basis of such links and identifying the sensors in this redox response are few.…”
Section: Mapk Signaling Under Oxidative Stressmentioning
confidence: 99%